Peranan Pharmaceutical Care dalam Meningkatkan Hasil Klinis dan Kualitas Hidup Pasien Penderita Diabetes Melitus - Syaripuddin, Muhammad (Jurnal Kefarmasian Indonesia, 2013)
Pharmaceutical care is patient oriented pharmacy practice that required other healthcare to optimize drug therapy. In the management of diabetes mellitus indicators was established as a target in pharmaceutical care. The purpose of this paper is to evaluate pharmaceutical care program, in order to optimize clinical result and quality of life of the patient diabetes mellitus, and to identify indicators in pharmaceutical care program for patient diabetes mellitus as well. Research of the impact of pharmaceutical care program for diabetes mellitus patient have been done in other countries. The results showed that diabetes mellitus indicators in patients managed with pharmaceutical care program were better than those without that program applied. All patients with intervention of pharmaceutical care program can control clinical result such as blood glucose, blood presure, level of HbA1C, HDL, LDL and total cholesterol. The patient’s quality of life with intervention had improved compare to those without intervention. Indicators to evaluate pharmaceutical care program have changed from clinical indicators only to clinical plus quality of life indicators. Pharmaceutical care program was useful to improve clinical result and quality of life of diabetic patient. Quality of life indicators could be added to evaluate pharmaceutical care program. Pharmaceutical care program brings about positif impact for patient, provider, pharmacist and economic aspect as well.